New approach to the technological aspect of corporate sustainable development - Rolandas Drejeris; Danguolė Oželienė (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Enterprises that seek for sustainable development should align economic interests with environmental and social requirements. It is not enough to take into account just these basics components. Technology plays a significant role in company activity. The aim of this article is to highlight the relationship between the dimensions characterising sustainability and to take a deeper look at the structure of the concept of sustainability, so that to understand in more detail the completeness of the dimensions of sustainability. For achieving this aim is necessary through the analysis of researchers' opinions to apply the logical assessment, systematisation, and comparison of information, selects the most important information describing the sustainability of technology, highlights the relationships between the technological aspect of sustainability and other sustainability dimensions, evaluates the technological processes of the corporate product in terms of sustainability, clarifies and presents arguments highlighting the importance of the technological aspect in sustainable business activity, rejects inappropriate arguments, identifies links between the arguments, and, basing on the information, proves and/or formulates anew some logical considerations to justify the full competency of the technological dimension in the sustainable development framework. Article proved that sustainable development contains the technological dimension which is added to the four classical dimensions and serves as an axis that determines the contents of other sustainability parts.
Keywords: C52; E61; O33; M20; Q56; Q01; 650; technology; sustainable activity; dimensions of sustainability; technological sustainability; sustainable business model